Pengaruh Penambahan Level Sari Buah Honje (Etlingera Elatior) dan Lama Penyimpanan Terhadap Kualitas Organoleptik, Fisik dan Total Mikroorganisme Sosis Ayam Petelur Afkir: Effect of Honje (Etlingera elatior) Fruit Juice Addition and Length of Storage on Organoleptic, Physical Quality and Total Microorganism of Cull Chicken Sausage. - Zulvanni, Talitha; Mudawaroch, Roisu Eny; Rinawidiastuti, Rinawidiastuti (Jurnal Riset Agribisnis dan Peternakan, 2024)
This study aims to determine the organoleptic, physical and total microorganism quality with the addition of different honje fruit juice. The treatments given were the addition of honje fruit juice as much as 0% (P0), 2.5% (P1), 5% (P2), and 7% (P3). This study used a completely randomized design (CRD) consisting of 4 treatments with 3 replications. The parameters taken were organoleptic test, physical test and total microorganisms. Organoleptic test consisted of taste, color, aroma and texture, physical test consisted of moisture content and pH. The results showed that the taste value of chicken sausage had a significant effect (P<0.05), namely 1.78; 2.89; 3.33; and 4.08. The color value of chicken sausage had a significant effect (P<0.05) of 2.96, 2.48, 2.37, and 2.15. The aroma value of chicken sausage had a significant effect (P<0.05) of 1.68, 2.79, 3.30, and 3.96. The texture value of chicken sausage had a significant effect (P<0.05) of 2.47, 2.91, 2.95 and 3.08. The moisture content value of chicken sausage had no significant effect (P>0.05), namely 28.00; 34.58; 34.33; and 33.50. The pH value of chicken sausage had a significant effect (P<0.05), namely 5.78, 5.47, 5.48, and 5.50. The total microorganisms produced were 7.1×107, 1.0×108, 1.1×108, and 1.5×108. It was concluded that the addition of honje fruit juice affected the organoleptic test and pH of the sausage. The addition of honje fruit juice had no effect on moisture content and total microbes. The suggestion is to conduct inhibition zone test against Staphylococcus aureus and Escherchia coli bacteria.